Antibody titers against the Alpha, Beta, Gamma, and Delta variants of SARS-CoV-2 induced by BNT162b2 vaccination measured using automated chemiluminescent enzyme immunoassay. Issue 2 (February 2022) - Kato, Hideaki; Miyakawa, Kei; Ohtake, Norihisa; Go, Hirofumi; Yamaoka, Yutaro; Yajima, Satoshi; Shimada, Tomoko; Goto, Atsushi; Nakajima, Hideaki; Ryo, Akihide
Abstract: Background: Levels of 50% neutralizing titer (NT50) reflect the a vaccine-induced humoral immunity after the vaccination against the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Measurements of NT50 are difficult to implement in large quantities. A high-throughput laboratory test is expected for determining the level of herd immunity against SARS-CoV-2. Methods: We analyzed samples from 168 Japanese healthcare workers who had completed two doses of the BNT162b2 vaccine. We analyzed immunoglobulin G (IgG) index values against spike protein (SP) using automated chemiluminescent enzyme immunoassay system AIA-CL and analyzed the background factors affecting antibody titer. SP IgG index was compared with 50% neutralization titers. Results: The median SP IgG index values of the subjects (mean age = 43 years; 75% female) were 0.1, 1.35, 60.80, and 97.35 before and at 2, 4, and 6 weeks after the first dose, respectively. At 4 and 6 weeks after the first dose, SP IgG titers were found to have positive correlation with NT50 titer (r = 0.7535 in 4 weeks; r = 0.4376 in 6 weeks). Proportions of the SP IgG index values against the Alpha, Beta, Gamma, and Delta variants compared with the original strain were 2.029, 0.544, 1.017, and 0.6096 respectively. Older age was associated with lower SP IgG titer index 6 weeks after the first dose. Conclusions: SP IgG index values were rised at 3 weeks after two doses of BNT162b2 vaccination and have positive correlation with NT50. SP IgG index values were lower in the older individuals and against Beta and Delta strain.